A new species of Pleurothallidinae (Orchidaceae) from the south-east of Ecuador - Baquero, Luis E.; Fierro Minda, Alison; Yeager, Justin (Lankesteriana: International Journal on Orchidology, 2020)
Porroglossum marcojimeneziorum, a new species of subtribe Pleurothallidinae, was discovered in Zamora Chinchipe province (South-East Ecuador) which is described here, including information about its phenology and ecology. Porroglossum marcojimeneziorum is compared with its most similar species, P. hirtzii, from which it differs by producing smaller flowers; the shortly-pubescent, triangular-ovate, obtuse lateral sepals and the blade of the lip obovate transversely expanded. Key words: Porroglossum marcojimeneziorum, Porroglossum hirtzii, Zamora Chinchipe